2019
DOI: 10.1039/c8ra09655d
|View full text |Cite
|
Sign up to set email alerts
|

Niosomes encapsulated in biohydrogels for tunable delivery of phytoalexin resveratrol

Abstract: A series of biohydrogels were evaluated as potential soft delivery vehicles for the encapsulation and subsequent release of niosomes loaded with resveratrol (RSV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 65 publications
3
10
0
1
Order By: Relevance
“…Tinnakorn et al(2017) reported that the cholesterol existing in niosome results in increased targeted drug delivery to bacteria through binding to bacteria's lipid membrane(52). Consistent with that of Machado and Akbari, results of the present study indicate increased antibacterial activity in nanomaterial-encapsulated antibiotics(53,54). According toGupta et al (2018), there are various absorption and fusion mechanisms between the niosome and the bacterial wall that could result in increased targeted drug delivery(55).…”
supporting
confidence: 90%
“…Tinnakorn et al(2017) reported that the cholesterol existing in niosome results in increased targeted drug delivery to bacteria through binding to bacteria's lipid membrane(52). Consistent with that of Machado and Akbari, results of the present study indicate increased antibacterial activity in nanomaterial-encapsulated antibiotics(53,54). According toGupta et al (2018), there are various absorption and fusion mechanisms between the niosome and the bacterial wall that could result in increased targeted drug delivery(55).…”
supporting
confidence: 90%
“…On the other hand, literature from the drug delivery field dealing with bioactive compounds loaded in liposomes, core-shell liposomes, niosomes with or without being encapsulated within biopolymeric hydrogels [59,73,74] determine release profiles using dialysis methods in physiologically relevant buffers rather than in vitro digestion models.…”
Section: Setting the Scene: Review Of Colloidal Delivery Vehiclesmentioning
confidence: 99%
“…For instance, the Korsmeyer-Peppas and Weibull models predicted anomalous transport (rather than typical Fickian diffusion) of resveratrol suggesting specific interactions between niosomes and hydrogel matrices [74]. Therefore, fitting in vitro release or bioaccessibility kinetics data to relevant mathematical models (Table 1) is providing useful quantitative comparison between different delivery vehicles in order to predict in vivo release kinetics and the release mechanisms.…”
Section: Setting the Scene: Review Of Colloidal Delivery Vehiclesmentioning
confidence: 99%
“…There is a general consensus that the future for efficient resveratrol delivery is based on obtaining systems capable of overcoming the limitations of this compound. There are a few reports based on the use of different delivery systems for the photoprotection of RSV, such as, self-nanoemulsions, core-shell nanoparticles, cyclodextrin complexes, hydrogels and lipid-core nanocapsules [ 18 , 34 , 35 ]. For instance, Fan et al developed RSV-loaded zein encapsulated with bovine serum albumin-caffeic acid conjugated core-shell nanoparticles.…”
Section: Introductionmentioning
confidence: 99%